Trends of social welfare systems: from convergence to attractiveness. An exploratory approach - RECWOWE; Bouget, Denis (Edinburgh, 2009)
"The analyses of the national reforms in the welfare states over the last decades were partly focused on this notion of convergence. In the eighties and the nineties, the transformation in many welfare states provided a literature on the retrenchment of the welfare states which explained the trends as a bottom race or a downward convergence. The economic literature has provided a large range of measurements of convergence in per capita GDP between countries. These indicators have mainly been based on the deviation measurement, the differences between growth rates, or the changes in the ranks of countries). The analyses on the convergence/divergence in the social welfare states often used the same indicators as in economic studies. In this exploratory paper we would like to re-think the measurement of convergence on the basis of attractiveness between pairs of countries because many national reforms have been inspired by the existence of specific policies in some leading countries which became 'models' for the other ones. This paper proposes a methodology for distinguishing the countries which are attracted by some other ones, from the countries which are attractors (models). The first results on OECD data partly contradict the idea of a downward convergence of the social welfare states in the eighties and the nineties."